Accute Toxicity of Extract From Melinjo (Gnetum Gnemon L) Leaf With Fixed Dose Procedure Method - Herlina Herlina; Annisa Amriani; Dina Permata Wijaya; Ayu Adelia Lestari (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Melinjo leaves has several benefits as antidiabetic, antihyperglycemia, antioxidant and diuretic. In this experiment the acute toxicity test of ethanol extract of melinjo (Gnetum gnemon L). leaves on male white rats of wistar strain with fixed dose procedure method. The result of the screening of the phytochemical showed that the leaves of beluntas contained alcaloid, flavonoid, saponin, fenolic, and tanin. Ethanol extract of melinjo leaves was obtained by maceration using ethanol 70%. From the observational study, the dose 2000 mg/kg BW was chosen as starting dose for the main study. Experimental animal subject used in the main study were 10 male white rats of wistar which were divided into 2 group, normal group and treatment group with a dose of 2000 mg/kgBW. The result showed that there were no death or toxicity sign in all experimental animals. During the 14 days observation period, there were no significant changes in body weight of rats either in normal control group and treatmen group with a dose of 2000 mg/kg BW (p>0.05). Melinjo leaves had no effect on the macroscopic organs of liver, kidneys and heart of the test animals (p>0.05). The average level of biochemical parameters in the normal group is SGOT 54.13±11.428 U/L, SGPT 47.476±21.655 U/L, creatinine 0.632±0.199 mg/dL, and urea 14.46±2.267 mg/dL, while the 2000 mg/kg BW dose group is SGOT 60.192±14.198 U/L, SGPT 55.968±22.998 U/L, creatinine 0.756±0.204 mg/dL, and urea 16±2.561 mg/dL. It showed that the ethanol extract of melinjo leaves with a dose of 2000 mg/kgBW are the category of practically non-toxic.